Predictive indices used for ventilatory weanning (Research, Society and Development, 2024)
Objective: The present study aims to mention the predictive indexes used for ventilatory weaning in scientific virtual databases from 2007 to 2024, articles related to the indexes and their importance in the intensive care unit. Methodology: A bibliographical search was carried out on the topics of interest through journals in the following databases: Scielo (Scientific Eletronic Library Online), VHL (Virtual Health Library), Google Academico, Pub Med (National Center for Biotechnology Information) Lilacs and Bireme, The papers reviewed were published between 2007 and 2024, in Portuguese and English, including clinical trials, case reports and abstracts. Results: The review included 20 original articles and available in full text, all duly published with databases and fulfilling the established criteria. All studies were performed whith the objective of identifying the predictive indexes used in ventilator weaning. Conclusion: Through this narrative review, it was cluncludes that the predictive indexes used for ventilator weaning offer more safety to the health professionals and the effectiveness of the patient’s treatment, being aware that the sorter the time spent in mechanical ventilation, the better their evolution.